20 Value of Serum Oxidative Stress and Metal Profiling for Post-Stroke Functional Recovery. (11th January 2018) - Rongioletti, Mauro; Squitti, Rosanna; Siotto, Mariacristina; Assenza, Giovanni; Granata, Giuseppe; Giannantoni, Nadia Mariagrazia; Zappasodi, Filippo; Giannantoni, Nadia Mariagrazia
Abstract: Background: Stroke patients' clinical course can be largely variable despite similar lesions and clinical states at symptoms' onset. We sought to identify new serum biomarkers for poststroke functional recovery. Methods: We assessed iron, copper, free copper, total antioxidant status (TAS), peroxides, ceruloplasmin (Cp) concentration and activity, ferritin, transferrin (Tf), Cp to Tf ratio (Cp:Tf), and Cp to copper ratio (Cp:Cu) in acute phase (2–10 days from symptoms onset [t0]) in 30 patients affected by stroke in the middle cerebral artery of a single hemisphere. Clinical severity at t0 and at t1 (stabilized phase, typically six months) was evaluated through the National Institute of Health Stroke Scale (NIH) score. Effective recovery (ER) was evaluated as the clinical condition reached in t1 with respect to the condition at symptom onset (NIH1-NIH0/NIH0). Results: In the acute phase (t0), clinical severity correlated with lower levels of TAS and iron, and with increased peroxide concentrations. At t1, clinical severity correlated with increased peroxide and ceruloplasmin concentrations. A worse ER correlated with higher levels of copper, free copper, Cp activity, and values of Cu:Cp. Conclusions: Analysis of oxidative stress and metal profiling of serum could be a useful tool in the search for early biomarkers of ischemic stroke recovery.